Chitosan-based polyion liquid optimized aqueous zinc ion battery electrolyte and preparation thereof

By using chitosan-based aprotic/protic polyion liquid as an electrolyte additive in aqueous zinc ion batteries, it inhibits dendrites' growth and improves solvation structure, and solves the uneven zinc deposition and high chemical reactivity in zinc ion batteries. The problem of achieving higher cycle life and coulomb efficiency reduces costs and side effects.

CN119170894APending Publication Date: 2024-12-20GUIZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411239056.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The disorderly migration and concentration polarization of zinc ions in traditional water-based zinc ion batteries lead to uneven zinc deposition, dendrite formation, short circuit failure, and the high chemical reactivity of water leads to hydrogen evolution reaction and pH increase, seriously damaging the cycle life of the battery and Coulomb efficiency, existing additives are costly and limited in functionality.

Method used

Chitosan-based aprotic/protic polyionic liquid is used as an electrolyte additive. Through its diverse groups and high number of active groups, dendrites can be inhibited, solvated structures can be improved, protective layers can be formed, active water can be reduced, and active water can be promoted. Zinc ion transmission improves battery performance.

Benefits of technology

It achieves longer cycle life and higher Coulomb efficiency, reduces additive usage and cost, improves the electrochemical performance and stability of the battery, and is suitable for the application of high-performance aqueous zinc ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170894A_ABST
    Figure CN119170894A_ABST
Patent Text Reader

Abstract

The invention discloses a chitosan-based polyion liquid optimized aqueous zinc ion battery electrolyte and a preparation method thereof. The preparation method comprises the following steps: 1, preparing an aqueous zinc ion battery electrolyte; 2, preparing a dilute acid solution; 3, adding chitosan into the dilute acid solution in the step 2 to obtain a chitosan-based aprotic / protic polyion liquid; and 4, adding the polyion liquid in the step 3 into the electrolyte in the step 1 to prepare the chitosan-based polyion liquid optimized aqueous zinc ion battery electrolyte. The electrolyte is optimized based on the chitosan-based aprotic / protic polyion liquid, is water-soluble, has various functional groups, has more groups per unit mass, has better performance in inhibiting dendritic crystal growth and improving the solvation structure of the electrolyte, and is less in addition amount, lower in cost and smaller in side effect; the method has important significance in promoting the application of the high-performance aqueous zinc ion battery; in addition, the electrolyte is simple in preparation process and easy to industrially implement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aqueous zinc ion battery electrolyte and a preparation thereof, in particular to a chitosan-based non-proton / proton type polyionic liquid optimized aqueous zinc ion battery electrolyte and a preparation thereof. Background Art

[0002] In recent years, under the guidance of national policies and market demand, the research on safe, green, low-cost, and high-performance rechargeable batteries has become particularly important. As the core component of energy storage, batteries play a key role in achieving the smooth output of renewable energy, the long driving range of electric vehicles, and the long-lasting endurance of mobile devices. Therefore, researchers are committed to developing new rechargeable batteries to meet the growing energy demand and environmental protection requirements.

[0003] Aqueous zinc-ion batteries (ZIBs) have attracted extensive attention in grid-scale energy storage systems due to their inherent safety and low cost. On the one hand, zinc metal anodes have abundant zinc resources, low price, and high theoretical capacity (820 mAh g -1 or 5855mAh cm -3 ) and other advantages; on the other hand, water as a solvent has the advantages of high safety (non-flammable and non-explosive), green environmental protection, and mild battery assembly conditions, which makes up for the huge difficulties faced by lithium-ion batteries and is the most promising new energy storage system. However, the disordered migration and concentration polarization of zinc ions in traditional aqueous electrolytes can lead to uneven zinc deposition, forming a loose and rough zinc deposition layer, which seriously damages the reversibility of the zinc anode. In addition, under the action of the local electric field, due to the "tip effect", zinc ions tend to deposit at the tip of the protrusion, further forming dendrites, piercing the diaphragm, and causing the battery to short-circuit and fail. The water molecules in the solvation structure of water have high chemical reactivity. During the charge and discharge process, the severe hydrogen evolution reaction (HER) not only consumes a large amount of electrolyte, but also rapidly increases the pH of the electrolyte and forms irreversible byproducts (Zn4SO4(OH)6·xH2O), which makes the cycle life and coulomb efficiency of aqueous zinc-ion batteries deteriorate sharply.

[0004] In order to solve the above problems, researchers have conducted in-depth research on zinc electrodes, diaphragms and electrolytes, and proposed a series of solutions. For example, zinc electrode component or structural design, artificial solid electrolyte interface layer, functionalized diaphragm, use of solid or semi-solid electrolytes, etc., but the above strategies, structural design and actual operation are relatively complex, the material construction cost is high, and it is difficult to achieve large-scale production, or the use of solid or semi-solid electrolytes, resulting in reduced ion conductivity and ion migration number, and serious damage to electrochemical performance, making it difficult to meet the requirements of practical applications. It is worth mentioning that since the electrolyte plays the role of connecting electrodes and transmitting ions in aqueous zinc-ion batteries, the use of low-cost, high-safety additives can change the physicochemical properties of the electrolyte on the basis of minimal side effects, thereby improving the various performance of the battery, and is expected to achieve large-scale production and application. Therefore, electrolyte additive engineering is one of the simplest and most effective strategies and is considered to be the best choice for regulating the electrochemical properties of aqueous zinc-ion batteries.

[0005] Electrolyte additives have multiple mechanisms of action in zinc-ion batteries, including improving the conductivity of the electrolyte, forming a stable interface layer, promoting ion transport and reaction rate, and inhibiting side reactions. Selecting appropriate additives and rationally regulating their concentrations can effectively improve battery performance. In the field of zinc-ion batteries, electrolyte additives play a vital role, as they can significantly improve battery performance and cycle stability. There are many types of these additives, each with its own unique mechanism of action.

[0006] So far, electrolyte additives such as dextran, gum arabic, glycine, and tripropylene glycol have been reported as aqueous zinc-ion battery additives to regulate the solvation structure, inhibit zinc dendrite growth, and reduce side reactions such as corrosion and hydrogen evolution. However, the additive groups reported so far are relatively simple and are relatively greatly affected by the dosage, which results in fewer additive functions and higher costs. In addition, the intrinsic safety of aqueous electrolytes is also compromised after adding a large amount of flammable organic solvents.

[0007] In addition, multiscale theoretical and experimental studies have shown that high-donor additives with strong electron-donating ability can limit free water activity and replace Zn 2+ The water solvation sheath in the aqueous ZnO2O3 reshapes the hydrogen bond network of water. It can significantly inhibit the hydrogen evolution and severe corrosion involved in water, which is conducive to the uniform deposition and long cycle life of aqueous Zn-ion batteries.

[0008] Chitosan is a natural polysaccharide, usually extracted from the shells of crustaceans. It is widely used in many biomedical and industrial applications. In addition, chitosan is a natural polymer material that can be naturally degraded in the environment and is eco-friendly. However, since the structural units of chitosan molecules contain abundant functional groups (-NH2 and -OH), they can form intramolecular and intermolecular hydrogen bonds. At the same time, chitosan has a high molecular weight and high crystallinity, so its solubility is relatively poor and requires specific conditions to dissolve. Since chitosan is almost insoluble in water directly, it is difficult to act as an electrolyte additive for aqueous zinc-ion batteries.

[0009] The patent with publication number CN114039109 discloses an additive for aqueous zinc ion battery electrolyte, wherein the additive is water-soluble chitosan. After adding the water-soluble chitosan to the aqueous zinc ion battery electrolyte, the growth of zinc dendrites in the electrolyte is inhibited and the free water activity is reduced, thereby improving the rate performance and cycle performance of the aqueous zinc ion battery. However, the current chitosan additives are mainly water-soluble chitosan derivatives, which do not achieve very outstanding effects in inhibiting dendrite growth and improving the electrolyte solvation structure. In addition, when the required performance is achieved, the amount of addition is large, which has a high cost on the one hand and affects other properties of the electrolyte on the other hand, and cannot meet the use requirements of high-performance aqueous zinc ion batteries.

[0010] Therefore, based on the above problems, the present invention aims to convert chitosan into a more powerful water-soluble chitosan-based non-proton / proton polyionic liquid through molecular engineering, so as to apply it to aqueous zinc ion battery electrolyte additives to solve the above-mentioned related problems. Summary of the invention

[0011] In order to solve the above technical problems, the present invention provides a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte and its preparation. The aqueous zinc ion battery electrolyte of the present invention is optimized based on chitosan-based non-proton / proton type polyionic liquid. The chitosan-based non-proton / proton type polyionic liquid is water-soluble, and has diverse functional groups, more groups per unit mass, better performance in inhibiting dendrite growth and improving electrolyte solvation structure, and less addition amount is required to achieve the same performance, lower cost, and less side effects, which is of great significance for promoting the application of high-performance aqueous zinc ion batteries; in addition, the electrolyte preparation process of the present invention is simple, easy to implement industrially, and worthy of wide promotion and application.

[0012] One of the technical solutions of the present invention:

[0013] A method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte comprises the following steps:

[0014] Step 1: Add a zinc source into water to prepare an aqueous zinc ion battery electrolyte;

[0015] Step 2: Add acidic substances into water to prepare a dilute acid solution;

[0016] Step 3: adding chitosan to the dilute acid solution obtained in step 2, stirring and dissolving, to obtain a chitosan-based aprotic / protic polyionic liquid;

[0017] Step 4: adding the chitosan-based non-protonic / protonic polyionic liquid obtained in step 3 to the electrolyte obtained in step 1 to prepare a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte.

[0018] Preferably, in the aforementioned chitosan-based polyionic liquid-optimized method for preparing an aqueous zinc ion battery electrolyte, the zinc source is any one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(CH3COO)2 or Zn(CF3SO3)2.

[0019] Preferably, in the method for preparing the aforementioned chitosan-based polyionic liquid-optimized aqueous zinc ion battery electrolyte, in step 1, the concentration of the zinc source in the aqueous zinc ion battery electrolyte is 0.001-3M.

[0020] Preferably, in the aforementioned chitosan-based polyionic liquid optimized method for preparing aqueous zinc ion battery electrolyte, the acidic substance in step 2 is one or any multiple of the non-protonic ionic liquids functionalized with carboxyl or sulfonic acid groups as shown below.

[0021]

[0022] Where: R is -(CH2) n -, n = 1-5; R1, R2 and R3 are CH3-(CH2) n -, n = 0-6; X is Cl or Br;

[0023]

[0024] Where: R is -(CH2) n -, n = 3 or 4; R1, R2 and R3 are CH3-(CH2) n -, n = 0-6; X is Cl or Br.

[0025] Preferably, in the aforementioned chitosan-based polyionic liquid-optimized aqueous zinc ion battery electrolyte preparation method, the acidic substance is any one or more of betaine hydrochloride, 1-(carboxymethyl)imidazole hydrochloride, 1-(sulfopropyl)imidazole hydrochloride, 1-(carboxymethyl)pyridine hydrochloride or 1-(sulfopropyl)pyridine hydrochloride.

[0026] Preferably, in the aforementioned method for preparing the chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte, in the step three, the molar ratio of the acidic substance to the chitosan is 1:1-3:1.

[0027] Preferably, in the aforementioned method for preparing the chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte, the stirring and dissolving in step 3 is performed at 20-80° C. for 1-10 hours.

[0028] Preferably, in the aforementioned method for preparing the chitosan-based polyionic liquid-optimized aqueous zinc ion battery electrolyte, in the step 4, after adding the chitosan-based polyionic liquid, the concentration of chitosan in the electrolyte is 0.1-10 g / L.

[0029] The second technical solution of the present invention:

[0030] A chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte prepared by the aforementioned method is prepared according to the method of the aforementioned scheme one.

[0031] One of the technical solutions of the present invention:

[0032] An aqueous zinc ion battery contains the above-mentioned chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte, and other battery components are consistent with traditional aqueous zinc ion battery components.

[0033] Beneficial effects of the present invention:

[0034] 1. The chitosan-based non-proton / proton polyionic liquid in the electrolyte of the present invention is completely different from the traditional polyionic liquid. It is a bio-based material, which is prepared using natural polymer material chitosan and acidic substances as raw materials. The preparation method is simple, the materials are easily available, and it is environmentally friendly.

[0035] 2. The present invention is the first to use chitosan-based non-proton / proton polyionic liquid to optimize the electrolyte of aqueous zinc-ion batteries. Compared with traditional water-soluble chitosan, it has a controllable molecular structure and more active groups, has greater application potential in the field of energy storage, and can better improve the long cycle life and coulombic efficiency of aqueous zinc-ion batteries.

[0036] 3. The chitosan-based non-proton / proton polyionic liquid used to optimize the aqueous zinc ion battery electrolyte of the present invention is composed of anions and polycations, wherein the anion and cation groups per unit mass are more, and the polycations are preferentially adsorbed on the zinc anode to form an N-containing interface protective layer, uniform zinc ion flux, and form a flat zinc deposition. Anions can participate in the solvation structure, reduce the content of active water molecules, and promote zinc ion transport kinetics. Through the synergistic effect of anions and cations, the cycle life and coulomb efficiency of aqueous zinc ion batteries can be better improved.

[0037] 4. The aqueous zinc ion battery electrolyte of the present invention contains less chitosan additives, has lower cost, less side effects, and better performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The synthetic chemical formulas of the chitosan-based aprotic / protic polyionic liquids using different acidic substances as anions obtained in Examples 2, 5 and 6 of the present invention are shown.

[0039] Figure 2 The scanning electron microscope image of the zinc foil after being immersed in the aqueous zinc ion battery electrolyte optimized by the chitosan-based non-proton / proton polyion liquid described in Comparative Example 1 (1M ZnSO4 solution), Example 1 and Example 2 for 15 days shows that a protective film is adsorbed on the surface of the zinc foil to which the chitosan-based non-proton / proton polyion liquid is added, which can isolate active water, uniform the electric field, and reduce side reactions such as zinc dendrite growth, hydrogen evolution and corrosion.

[0040] Figure 3 The zinc battery assembled with the aqueous zinc ion battery electrolyte optimized by chitosan-based aprotic / protic polyionic liquid described in Comparative Example 2 (1M Zn(CF3SO3)2 solution), Example 9, Example 10 and Example 11 of the present invention, at a current density of 1 mA cm -2 , 1mAhcm -2 The long cycle life diagram under the conditions of . It can be seen that the battery with the addition of chitosan-based non-protonic / protonic polyionic liquid has a longer cycle life.

[0041] Figure 4 The zinc battery assembled with the aqueous zinc ion battery electrolyte optimized by chitosan-based aprotic / protic polyionic liquid described in Comparative Example 3 (1M ZnCl2 solution) and Example 10 of the present invention was tested at a current density of 1 mA cm -2 , 1mAhcm -2 Long cycle diagram after aging for 24 hours under the conditions of . It can be seen that the battery cycle stability is greatly improved by adding chitosan-based non-protonic / protonic polyionic liquid.

[0042] Figure 5The zinc battery assembled with the aqueous zinc ion battery electrolyte optimized by chitosan-based non-proton / proton type polyionic liquid described in comparative example 2 (1MZn(CF3SO3)2 solution) and Example 9 was tested for electrochemical impedance spectroscopy at different temperatures, and the activation energy was obtained by linear fitting. It can be seen that the battery with the addition of chitosan-based non-proton / proton type polyionic liquid has improved the electrochemical performance of the battery.

[0043] Figure 6 The rate performance tests of the zinc batteries assembled with the aqueous zinc ion battery electrolyte optimized by the chitosan-based non-proton / proton type polyion liquid described in Comparative Example 1 (1MZnSO4 solution) and Example 2 of the present invention under different current density conditions show that the battery with the addition of chitosan-based non-proton / proton type polyion liquid has stronger voltage stability and effectively improves the reversibility of zinc ion deposition / stripping.

[0044] Figure 7 From the SEM scanning electron microscope image of the zinc anode of the zinc battery assembled with the aqueous zinc ion battery electrolyte optimized by the chitosan-based non-proton / proton polyion liquid described in Example 2 of the present invention after a long zinc cycle, it can be seen that a protective layer is formed on the surface of the zinc anode of the battery to which the chitosan-based non-proton / proton polyion liquid is added, which can effectively uniformize the electric field and improve the electrochemical performance of the zinc ion battery.

[0045] Figure 8 The aqueous zinc ion battery electrolyte optimized by chitosan-based non-proton / proton polyion liquid described in Comparative Example 1 (1M ZnSO4 solution), Example 2, Example 5 and Example 6 of the present invention, a pure zinc sheet is immersed in the SEM scanning electron microscope image of the zinc anode after a long zinc cycle. It can be seen that a protective layer is formed on the surface of the zinc anode of the battery to which the chitosan-based non-proton / proton polyion liquid is added, which can effectively uniform the electric field and improve the electrochemical performance of the zinc ion battery.

[0046] Fig. 9 From the electrochemical impedance diagrams of the zinc batteries assembled with the aqueous zinc ion battery electrolyte optimized by the chitosan-based non-proton / proton type polyion liquid described in Comparative Example 1 (1MZnSO4 solution), Example 2, Example 5 and Example 6 of the present invention after standing for different periods of time, it can be seen that the impedance of the battery to which the chitosan-based non-proton / proton type polyion liquid is added gradually becomes stable with the increase of time, indicating that its internal electrochemical environment is very stable.

[0047] Fig.10From the Raman test graphs of the aqueous zinc ion battery electrolyte optimized by chitosan-based non-proton / proton type polyionic liquid described in Comparative Example 1 (1MZnSO4 solution), Example 2, Example 5 and Example 6 of the present invention, it can be seen that the hydrogen bonds of the electrolyte added with chitosan-based non-proton / proton type polyionic liquid change to a decrease in strong hydrogen bonds, an increase in medium hydrogen bonds, and a decrease in weak hydrogen bonds. This proves that the addition of chitosan-based non-proton / proton type polyionic liquid reconstructs the hydrogen bond network inside the electrolyte and improves the electrochemical performance of the aqueous zinc ion battery. DETAILED DESCRIPTION

[0048] The present invention will be further described below in conjunction with the embodiments, but they are not intended to limit the present invention.

[0049] Embodiments of the present invention

[0050] Comparative Example 1 of the present invention

[0051] Add 3.23 g of zinc sulfate and an appropriate amount of deionized water to a 20 mL volumetric flask and fully dissolve at room temperature to obtain a 1 M ZnSO4 solution.

[0052] Comparative Example 2 of the present invention

[0053] Add 7.27 g of zinc trifluoromethanesulfonate and an appropriate amount of deionized water to a 20 mL volumetric flask and fully dissolve at room temperature to obtain a 1 M Zn(CF3SO3)2 solution.

[0054] Comparative Example 3 of the present invention

[0055] Add 2.73 g zinc chloride and an appropriate amount of deionized water to a 20 mL volumetric flask and fully dissolve at room temperature to obtain a 1 M ZnCl2 solution.

[0056] Embodiment 1 of the present invention

[0057] (1) Weigh 16.1 mg of betaine hydrochloride and dissolve it in an appropriate amount of deionized water to obtain an acidic solution.

[0058] (2) Weigh 18 mg of chitosan and add it to the acidic solution in step (1) to prepare 10 mL of chitosan-based aprotic / protic polyionic liquid.

[0059] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0060] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 0.9 g / L -1 Aqueous zinc-ion battery electrolyte.

[0061] Embodiment 2 of the present invention

[0062] (1) Weigh 32.2 mg of betaine hydrochloride and dissolve it in an appropriate amount of deionized water to obtain an acidic solution.

[0063] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to prepare 10 mL of chitosan-based aprotic / protic polyionic liquid.

[0064] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0065] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0066] Embodiment 3 of the present invention

[0067] (1) Weigh 64.3 mg of betaine hydrochloride and dissolve it in an appropriate amount of deionized water to obtain an acidic solution.

[0068] (2) Weigh 72 mg of chitosan and add it to the acidic solution in step (1) to prepare 10 mL of chitosan-based aprotic / protic polyionic liquid.

[0069] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0070] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid in an amount of 3.6 g / L -1 Aqueous zinc-ion battery electrolyte.

[0071] Embodiment 4 of the present invention

[0072] (1) Weigh 128.6 mg of betaine hydrochloride and dissolve it in an appropriate amount of deionized water to obtain an acidic solution.

[0073] (2) Weigh 144 mg of chitosan and add it to the acidic solution in step (1) to prepare 10 mL of chitosan-based aprotic / protic polyionic liquid.

[0074] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0075] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 7.2 g / L-1 Aqueous zinc-ion battery electrolyte.

[0076] The cycle performance of the symmetric Zn / / Zn battery prepared with the aqueous zinc ion battery electrolyte obtained in Examples 1-4 is shown in Table 1.

[0077] Table 1 Comparison of cycling performance of symmetric Zn / / Zn batteries with different addition amounts of chitosan-based aprotic / protic polyionic liquids

[0078]

[0079]

[0080] Embodiment 5 of the present invention

[0081] (1) According to Example 2, 1-(carboxymethyl)imidazole hydrochloride was weighed at a molar ratio of 1:1 to chitosan and dissolved in 10 mL of deionized water to obtain an acidic solution.

[0082] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0083] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0084] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0085] Embodiment 6 of the present invention

[0086] (1) According to Example 2, 1-(sulfopropyl)imidazole hydrochloride was weighed at a molar ratio of 1:1 to chitosan and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0087] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0088] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0089] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0090] Embodiment 7 of the present invention

[0091] (1) According to Example 2, 1-(carboxymethyl)pyridine hydrochloride was weighed at a molar ratio of 1:1 to chitosan and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0092] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0093] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0094] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0095] Embodiment 8 of the present invention

[0096] (1) According to Example 2, 1-(sulfopropyl)pyridine hydrochloride was weighed at a molar ratio of 1:1 to chitosan and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0097] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0098] (3) Prepare 3.23 g of zinc sulfate into 10 mL of aqueous solution.

[0099] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), and stir evenly to obtain a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0100] The cycling performance comparison of symmetric Zn / / Zn batteries prepared with the aqueous zinc ion battery electrolytes obtained in Examples 5-8 is shown in Table 2.

[0101] Table 2 Comparison of the cycling performance of symmetric Zn / / Zn batteries prepared by using chitosan-based aprotic / protic polyionic liquids with different acidic substances

[0102] Types of acidic substances Cycle life (h) <![CDATA[Test conditions (mAcm -2 / mAhcm -2 )]]> Betaine hydrochloride 5320 1 / 0.5 1-(Carboxymethyl)imidazole hydrochloride 3605 1 / 0.5 1-(Sulfopropyl)imidazole hydrochloride 3154 1 / 0.5 1-(Carboxymethyl)pyridine hydrochloride 2410 1 / 0.5 1-(Sulfopropyl)pyridine hydrochloride) 2289 1 / 0.5

[0103] Embodiment 9 of the present invention

[0104] (1) According to Example 2, betaine hydrochloride was weighed at a molar ratio of 1:1 with chitosan, and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0105] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0106] (3) 7.27 g of zinc trifluoromethanesulfonate was prepared into 10 mL of aqueous solution.

[0107] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), stir evenly, and prepare a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0108] Embodiment 10 of the present invention

[0109] (1) According to Example 2, betaine hydrochloride was weighed at a molar ratio of 1:1 with chitosan, and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0110] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0111] (3) Prepare 2.73 g of zinc chloride into 10 mL of aqueous solution.

[0112] (4) Add the chitosan-based non-proton / proton type polyionic liquid in step (2) to the zinc sulfate solution in step (3), stir evenly, and prepare a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0113] Embodiment 11 of the present invention

[0114] (1) According to Example 2, betaine hydrochloride was weighed at a molar ratio of 1:1 with chitosan, and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0115] (2) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0116] (3) Prepare 3.67 g of zinc acetate into 10 mL of aqueous solution.

[0117] The chitosan-based non-proton / proton type polyionic liquid in step (2) is added to the zinc sulfate solution in step (3) and stirred evenly to obtain a chitosan-based non-proton / proton type polyionic liquid in an amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0118] Embodiment 12 of the present invention

[0119] (4) According to Example 2, betaine hydrochloride was weighed at a molar ratio of 1:1 with chitosan, and dissolved in an appropriate amount of deionized water to obtain an acidic solution.

[0120] (5) Weigh 36 mg of chitosan and add it to the acidic solution in step (1) to obtain a chitosan-based aprotic / protic polyionic liquid.

[0121] (6) Prepare 5.24 g of zinc perchlorate into 10 mL of aqueous solution.

[0122] The chitosan-based non-proton / proton type polyionic liquid in step (2) is added to the zinc sulfate solution in step (3), and stirred evenly to prepare a chitosan-based non-proton / proton type polyionic liquid with an addition amount of 1.8 g / L -1 Aqueous zinc-ion battery electrolyte.

[0123] The cycling performance comparison of symmetric Zn / / Zn batteries prepared with aqueous zinc ion battery electrolytes prepared in Examples 9-12 is shown in Table 3.

[0124] Table 3 Comparison of cycling performance of symmetric Zn / / Zn batteries with different zinc salts

[0125] Zinc salt types Cycle life (h) <![CDATA[Test conditions (mAcm -2 / mAhcm -2 )]]> <![CDATA[Zinc sulfate (ZnSO4)]]> 5320 1 / 0.5 <![CDATA[Zinc trifluoromethanesulfonate (Zn(CF3SO3)2)]]> 1800 1 / 0.5 <![CDATA[Zinc chloride (ZnCl2)]]> 960 1 / 0.5 <![CDATA[Zinc acetate (Zn(CH3COO)2)]]> 1064 1 / 0.5 <![CDATA[Zinc perchlorate (Zn(ClO4)2)]]> 1836 1 / 0.5

[0126] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and inventive concepts of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte, characterized in that: The steps include: Step 1: Add a zinc source into water to prepare an aqueous zinc ion battery electrolyte; Step 2: Add acidic substances into water to prepare a dilute acid solution; Step 3: adding chitosan to the dilute acid solution obtained in step 2, stirring and dissolving, to obtain a chitosan-based aprotic / protic polyionic liquid; Step 4: adding the chitosan-based non-proton / proton polyionic liquid obtained in step 3 to the electrolyte obtained in step 1 to prepare a chitosan-based non-proton / proton polyionic liquid optimized aqueous zinc ion battery electrolyte.

2. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The zinc source is any one or more of ZnSO4, ZnCl2, Zn(ClO4)2, Zn(CH3COO)2 or Zn(CF3SO3)2.

3. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The concentration of the zinc source in the aqueous zinc ion battery electrolyte in step 1 is 0.001-3M.

4. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: In step 2, the acidic substance is one or more of the non-protonic ionic liquids functionalized with carboxyl or sulfonic acid groups as shown below: Where: R is -(CH2) n -, n = 1-5; R1, R2 and R3 are CH3-(CH2) n -, n = 0-6; X is Cl or Br; Where: R is -(CH2) n -, n = 3 or 4; R1, R2 and R3 are CH3-(CH2) n -, n = 0-6; X is Cl or Br.

5. The method for preparing the chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 4, characterized in that: The acidic substance is one or more of betaine hydrochloride, 1-(carboxymethyl)imidazole hydrochloride, 1-(sulfopropyl)imidazole hydrochloride, 1-(carboxymethyl)pyridine hydrochloride or 1-(sulfopropyl)pyridine hydrochloride.

6. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: In the step three, the molar ratio of the acidic substance to chitosan is 1:1-3:

1.

7. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: The stirring and dissolving in step 3 is performed by stirring at 20-80° C. for 1-10 hours.

8. The method for preparing a chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte according to claim 1, characterized in that: In the step 4, after adding the chitosan-based non-proton / proton type polyionic liquid, the concentration of chitosan in the electrolyte is 0.1-10 g / L.

9. A chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte prepared according to the method according to any one of claims 1 to 8.

10. An aqueous zinc ion battery, characterized in that: Contains the chitosan-based polyionic liquid optimized aqueous zinc ion battery electrolyte as claimed in claim 9.

Citation Information

Cited By

  • Ionic liquid modified boehmite as well as preparation method and application thereof

    CN122301233A

  • Ionic liquid modified boehmite, preparation method and application thereof

    CN122301233B